Screening Of Fatty Acid Compound Of S. Polycystum For Anti-Cariogenic Potential - Zamimi, Nurul Najwa; Ab.Halim, Noorhazayti; Lestari, Widya; Darnis, Deny Susanti; Wan Ishak, Wan Mohd Faizal; Md Mustafa, Md Muziman Syah (IIUM Medical Journal Malaysia, 2017)
Introduction: Dental caries is the most common yet preventable disease. Study found that seaweed exhibits anti-cariogenic properties. However, little attention have been given to the study on anticariogenic properties of seaweed and the bioactive compound that responsible for the anticariogenic activities have not adequately investigated. This study was conducted to evaluate the best extraction methods for S. polycystum and to determine the fatty acid compounds of S. polycystum that have anti-cariogenic potential against oral cariogenic bacteria. Materials and Methods: Dried seaweeds were extracted by soxhlet using three different solvents (methanol, dichloromethane and hexane). The crude extracts were kept in a close container at -20 degree Celsius. The bioactive compound of the crude extract of seaweeds was analyzed using Gas Chromatography Mass Spectrometer (GCMS). Results: Highest extraction yield in S. polycystum was produced by methanol extraction followed by hexane and dichloromethane. GCMS analysis revealed that the presence of palmitic acid (18.02%) as major compound, followed by oleic acid (8.44%), lauric acid (5.23%), myristic acid (3.60%), heptadecanoic acid (2.23%), 9-hexadenoic acid (1.82%) and the lowest is 2-methylhexadecan-1-ol (1.75%). Conclusion(s): Methanol extraction is the most efficient solvent as it produced the highest extraction yield in S. polycystum.Lauric acid, palmitic acid, myristic acid and oleic acid detected in S. polycystum have been reported to exhibit antimicrobial activities thus proved the potentiality of S. polycystum as anti-cariogenic agent.